The 16th term of an Ap is 93 while the 25th term is 173 find the

19th term
Sum of 13th and 56th term
Product of 6th and 13th term

1 answer

To solve the problem, we need to remember the formula for the \(n\)th term of an arithmetic progression (AP), which is given by:

\[ a_n = a + (n-1)d \]

where \(a\) is the first term, \(d\) is the common difference, and \(n\) is the term number.

We are given:

  • The 16th term \(a_{16} = 93\)
  • The 25th term \(a_{25} = 173\)

Using the formula for the 16th term:

\[ a + 15d = 93 \quad \text{(1)} \]

Using the formula for the 25th term:

\[ a + 24d = 173 \quad \text{(2)} \]

Next, we will subtract equation (1) from equation (2) to eliminate \(a\):

\[ (a + 24d) - (a + 15d) = 173 - 93 \] \[ 24d - 15d = 80 \] \[ 9d = 80 \] \[ d = \frac{80}{9} \]

Now that we have \(d\), we can substitute \(d\) back into either equation to find \(a\). We'll use equation (1):

\[ a + 15\left(\frac{80}{9}\right) = 93 \] \[ a + \frac{1200}{9} = 93 \] \[ a = 93 - \frac{1200}{9} \] Converting \(93\) to a fraction with a denominator of \(9\):

\[ 93 = \frac{837}{9} \] Now substituting in:

\[ a = \frac{837}{9} - \frac{1200}{9} = \frac{837 - 1200}{9} = \frac{-363}{9} = -\frac{121}{3} \]

Now, we have \(a = -\frac{121}{3}\) and \(d = \frac{80}{9}\).

Finding the 19th Term

Now we can find the 19th term \(a_{19}\):

\[ a_{19} = a + (19-1)d = a + 18d \] \[ a_{19} = -\frac{121}{3} + 18\left(\frac{80}{9}\right) \] Calculating \(18 \times \frac{80}{9}\):

\[ 18 \times \frac{80}{9} = \frac{1440}{9} \]

Now substituting back:

\[ a_{19} = -\frac{121}{3} + \frac{1440}{9} \]

Converting \(-\frac{121}{3}\) to have the same denominator as \(\frac{1440}{9}\):

\[ -\frac{121}{3} = -\frac{363}{9} \] Thus,

\[ a_{19} = -\frac{363}{9} + \frac{1440}{9} = \frac{1440 - 363}{9} = \frac{1077}{9} \]

Sum of the 13th and 56th Terms

Finding the 13th term \(a_{13}\):

\[ a_{13} = a + 12d = -\frac{121}{3} + 12\left(\frac{80}{9}\right) = -\frac{121}{3} + \frac{960}{9} \] Converting \(-\frac{121}{3}\) again:

\[ -\frac{121}{3} = -\frac{363}{9} \] So,

\[ a_{13} = -\frac{363}{9} + \frac{960}{9} = \frac{960 - 363}{9} = \frac{597}{9} \]

Now finding the 56th term \(a_{56}\):

\[ a_{56} = a + 55d = -\frac{121}{3} + 55\left(\frac{80}{9}\right) = -\frac{121}{3} + \frac{4400}{9} \] Converting \(-\frac{121}{3}\):

\[ a_{56} = -\frac{363}{9} + \frac{4400}{9} = \frac{4400 - 363}{9} = \frac{4037}{9} \]

Now calculating the sum:

\[ a_{13} + a_{56} = \frac{597}{9} + \frac{4037}{9} = \frac{4634}{9} \]

Product of the 6th and 13th Terms

Finding the 6th term \(a_{6}\):

\[ a_{6} = a + 5d = -\frac{121}{3} + 5\left(\frac{80}{9}\right) = -\frac{121}{3} + \frac{400}{9} \] Converting \(-\frac{121}{3}\):

\[ -\frac{121}{3} = -\frac{363}{9} \]

Thus,

\[ a_{6} = -\frac{363}{9} + \frac{400}{9} = \frac{400 - 363}{9} = \frac{37}{9} \]

Now we already have \(a_{13} = \frac{597}{9}\).

Calculating the product:

\[ a_{6} \times a_{13} = \frac{37}{9} \times \frac{597}{9} = \frac{37 \times 597}{81} \]

Calculating \(37 \times 597 = 22089\).

Thus,

\[ \text{Product} = \frac{22089}{81} \]

Summary of Results

  1. The 19th term is \(\frac{1077}{9}\).
  2. The sum of the 13th and 56th terms is \(\frac{4634}{9}\).
  3. The product of the 6th and 13th terms is \(\frac{22089}{81}\).